Body of regulations of the practice of school management in Spain - Javier Murillo Torrecilla; Rocío García Peinado; Pilar Ortega Marcelo (ADIDE Federación, 2010)
The Education Act of 2006 (LOE) orders the compulsory assessment of headmasters of public schools at the end of their management period. The result of this evaluation will have, at least, economical consequences. This Act also states that the regional education authorities will be in charge of the development of such assessments. So has been done, and, as a result, nowadays there are as many evaluation programmes as autonomous communities. This article researches and compares the legal regulations in force that rule these evaluations in every autonomous community and finally shows that, in spite of its common origin and purpose, the systems, methods and evaluation processes which are used by the regional authorities differ greatly from each others. This analysis also draws some conclusions that could be taken into account to improve the evaluation process of headmasters.